Abordagem de ensino de língua inglesa por meio de conteúdos e formação de professores : apropriações, possibilidades e limitações - Alencar, João Gabriel de Conte Carvalho de (2016)
This study aims at investigating the possibilities, limitations and appropriations of the Content and Language Integrated Learning approach (CLIL or AECL in Portuguese – Abordagem de Ensino de Conteúdos diversos por meio da Língua) (for example COYLE; HOOD; MARSCH, 2010) for the teaching of English as an additional language in the current Brazilian educational scenario. In order to do so, the study analyzes evidence from a teacher education course of a Federal University located in Southern Brazil as well as beliefs of pre-service teachers in this course. The methodology is hybrid, triangulating both quantitative and, predominantly, qualitative data (DORNYEI, 2007) and is based on the exploratory research method (GIL, 2002). Data collection instruments include documental research, interviews and questionnaires applied to the students and to the professor in charge of the Supervised Practicum Course as well as the analysis of the class plans produced by the pre-service teachers in this course. The analysis of the course indicates that CLIL is not explicitly included in the curriculum. The analysis of the questionnaires and interviews suggests that though CLIL may provide benefits, its use is seen by preservice teachers as a great challenge in the current educational scenario, since it requires a professional contingent that is incompatible with the national reality once it demands language professionals who are able to teach various contents and viceversa. The analysis of the interview showed that the production of courseware based on CLIL requires a great amount of time and investment in teacher education and qualification in general and in the foreign language in particular. Finally, the analysis of the class plans suggests there is an intention to appropriate the CLIL approach in the class plans, though the plans are still structuralist in nature. The results of the study suggest that CLIL represents a relevant potential for the teaching of additional languages, but it requires more investment in teacher education, qualification and appreciation in general and in foreign language teacher education in particular. The study suggests a gradual implementation of CLIL in the Brazilian elementary education in combination with other approaches which can be used simultaneously or after CLIL, as well as the collaboration between language and contents teachers.